Is early chemical thromboprophylaxis in patients with solid organ injury a solid decision?. Issue 5 (November 2019) - Skarupa, David; Hanna, Kamil; Zeeshan, Muhammad; Madbak, Firas; Hamidi, Mohammad; Haddadin, Zaid; Northcutt, Ashley; Gries, Lynn; Kulvatunyou, Narong; Joseph, Bellal
Abstract : BACKGROUND: The optimal time to initiate chemical thromboprophylaxis (CTP) in patients who have undergone nonoperative management (NOM) of blunt solid organ injuries (SOI) remains controversial. The aim of our study was to assess the impact of early initiation of CTP in patients with blunt abdominal SOIs. METHODS: We performed a 2-year (2013–2014) retrospective analysis of American College of Surgeons Trauma Quality Improvement Program. We included all adult trauma patients (age, ≥ 18 years) with blunt SOI who underwent NOM. Patients were stratified into three groups based on timing of CTP (early, ⩽48 hours of injury; late, >48 hours of injury, ; and no prophylaxis group). Our primary outcomes were rates of failure of NOM, pRBC transfusion, and mortality. Our secondary outcomes were the rate of venous thromboembolic (VTE) events (i.e., deep venous thrombosis [DVT] and/or pulmonary embolism [PE]) and length of stay. RESULTS: A total of 36, 187 patients met the inclusion criteria. Mean age was 49.5 ± 19 years and 36% of patients received CTP (early, 37% (n = 4, 819) versus late, 63% (n = 8, 208)). After controlling for confounders, patients receiving early CTP had lower rates of DVT ( p = 0.01) and PE ( p = 0.01) compared with the no prophylaxis and late CTP groups. There was no difference between the three groups regarding the postprophylaxis pRBC transfusions, failure of NOM, and mortality. CONCLUSION: Our results suggest that in patients undergoing NOM of blunt abdominal SOI, early initiation of CTP should be considered. It is associated with decreased rates of DVT and PE, with no significant difference in post prophylaxis pRBC transfusion, failure of nonoperative management, and mortality. LEVEL OF EVIDENCE: Therapeutic, level V. Abstract : Supplemental digital content is available in the text.